Seni Gerak dalam Pertunjukan Wayang Tinjauan Estetika - Darmoko, Darmoko (Makara Human Behavior Studies in Asia, 2004)
Movement art in the puppet performances is often mentioned as sabetan. Puppet movement art, that contains rules, norms, guidance (orientation) is convention that is observed and referred to guidance the dalang artists when they move the puppets. One of the convention of movement in the puppet performance is udanagara. Udanegara, that contains ethics and aesthetic, is the rules of speaking, attitude, and action for actors in the puppet performance. Puppet movement include among others paying homage, walking, running, dancing, flying and fighting. That puppet movement is based on social class of puppet, age of puppet, class of puppet, and mood of expression of puppet. Therefore, the movement art of the puppet adopts basic wiraga (true or false action in the puppet movement), wirasa (true or false feeling of puppet movement), and wirama (true or false rhythm in the puppet movement). Method in this research will be conducted step by step: collection data (to watch of puppet performance on television, live performance, dialogue with dalang artist), analysis of data, literary research, conclusion and reporting of the research. This research concludes: puppet movement has of two meanings, large (totality of puppet movement) and narrow (fighting); puppet movement refers to the conventions (norms), oriented by dalang artists (udanegara); basic of puppet movement refers to social class of puppet, age of puppet, class of puppet, and mood of expression of puppet; now, puppet movement becomes more and more creative and dynamic. The development of puppet movement in line with the way of thinking of society that is more improved, critical, and dynamic.